A Novel Bioflocculant from Raoultella planticola Enhances Removal of Copper Ions from Water. (23rd July 2020) - Zeng, Fancheng; Xu, Liang; Sun, Caiyun; Liu, Hong; Chen, Libo
Abstract : Copper is one of the most toxic heavy metals. In this work, a sampling survey of copper ions in the water of Songhua River flowing through the chemical and living areas of Jilin City was studied. A new bioflocculant from Raoultella planticola was obtained. The investigation of Songhua River flowing through Jilin City shows that the copper concentration is between 0.07 ppb and 0.16 ppb. The bioflocculant supporting graphite oxide (GO) as a bioflocculant inducer used in this study has been utilized in treatment of copper ions in water. GO and bioflocculant infrared radiation (IR) spectrum and zeta potential were studied. Flocculational conditions of copper ion (0.2 ppm) were modeled and optimized using RSM (response surface methodology). Our data showed that flocculation efficiency was over 80%. Significant influencing factors and variables were pH, flocculation time, bioflocculant dosage, and GO inducer which had major impact effects on flocculation efficiency. The highest flocculation efficiency which is 86.01% was achieved at pH = 5, at 1.62 h and 13.11 mg bioflocculant with 13.11 mg GO as an inducer. However, temperature (A) and GO inducer were significant impact factors on the flocculation efficiency.